Electrochemical Impedance Spectroscopy Microsensor Based on Molecularly Imprinted Chitosan Film Grafted on a 4-Aminophenylacetic Acid (CMA) Modified Gold Electrode, for the Sensitive Detection of Glyphosate - Zouaoui, Fares; Bourouina-Bacha, Saliha; Bourouina, Mustapha; Alcacer, Albert; Bausells, Joan; Jaffrezic-Renault, Nicole; Zine, Nadia; Errachid, Abdelhamid (Frontiers in Chemistry, 2021)
A novel electrochemical impedance spectroscopy (EIS) microsensor has been constructed for the sensitive detection of the herbicide, glyphosate, in water. It was based on covalent immobilization of molecularly imprinted chitosan on the microelectrode surface previously modified with 4-aminophenylacetic acid (CMA). The resulting microelectrodes were characterized by using cyclic voltammetry measurement (CV), electrochemical impedance spectrometry (EIS) and scanning electron microscopy (SEM). Electrochemical Impedance Spectroscopy (EIS) increased with increasing the concentration of GLY from 0.31 pg/ml to 50 ng/ml indicating a good correlation. The detection limit of GLY was 1 fg/ml (S/N=3). Moreover, this microsensor showed good repeatability, selectivity, reproducibility and was successfully used for the determination of GLY in river water samples.